Phytochemical And Pharmacological Review On Cassia Fistula Linn. - Sachin; Garg, Naresh Kumar (International Research Journal of Ayurveda & Yoga, 2021)
Cassia fistula (Aragvadhah) is an important drug used in the Indian system of medicine. It is a medium sized deciduous tree with long and cylindrical fruits containing pulp and also with a bright yellow colored flower. The tree is found throughout India in all deciduous forests and hilly tracts. The present article gives an account of updated information on its phytochemical and pharmacological properties. The review reveals that wide numbers of phytochemical constituents have been isolated from the plant which possesses activities like antiperiodic, diuretic, purgative, laxative, anti-asthmatic, hepatoprotective, anti-allergic and various other important medicinal properties. Phytochemical and Pharmacological reviews on plants will give valuable information which will assist the scientists in getting more advanced knowledge about a plant species.